Choice of diagnostic method for liver‐type glycogen storage disease. Issue 10 (17th October 2022) - Kakiuchi, Toshihiko; Zhang, Yumeng
Abstract: Liver biopsy is a highly invasive in nature, and measurement of enzyme activity in blood cells and the Fernandez test are less certain for the diagnosis of glycogen storage disease (GSD). Therefore, genetic testing, which can also identify typing, should be prioritized for the diagnosis of GSD. Abstract : From the aspect of certainty and safety, genetic testing, which can also identify typing, should be prioritized for the diagnosis of glycogen storage disease.